Anthropogenic gadolinium in freshwater and drinking water systems - Brünjes, Robert; Hofmann, Thilo (Water research (Oxford), 2020)
The increasing use of gadolinium-based contrast agents (GBCAs) for magnetic resonance imaging is leading to widespread contamination of freshwater and drinking water systems. Contrary to previous assumptions that GBCAs are stable throughout the water cycle, they can degrade. The stability of GBCAs depends largely on their organic ligands, but also on the physicochemical conditions. There is specific concern regarding UV end-of-pipe water treatments, which may degrade GBCAs. Degradation products in drinking water supplies can increase the risk of adverse health effects. This is of particular relevance where the raw water for drinking water production has a higher proportion of recycled wastewater. GBCAs concentrations in aquatic systems, often referred to as anthropogenic gadolinium, are determined using a variety of calculation methods. Where anthropogenic gadolinium concentrations are low, the inconsistent use of these methods results in high discrepancies and high levels of uncertainty. The current COVID-19 crisis will, in the short-term, drastically decrease the input of GBCAs to freshwater systems. Temporal variations in anthropogenic gadolinium concentrations in river water can be used to better understand river-aquifer interactions and groundwater flow velocities. Collecting urine from all patients following MRI examinations could be a way forward to halt the generally increasing concentrations of Gd in drinking water systems and recover this technologically critical element. [Display omitted] •Rising concentration of gadolinium-based contrast agents (GBCAs) in drinking water.•Stability of GBCAs is determined by their organic ligands.•UV end-of-pipe treatment may enhance the risks posed by GBCAs in drinking water.•Inconsistent use of methods to calculate Gd anomalies and anthropogenic Gd.•Temporal Gd patterns in rivers can improve understanding of subsurface systems.